Wheat gluten films prepared at high temperature and low pH decrease degradation by rumen microorganisms - K. Blaine; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2010)
Encapsulated amino acids, vitamins, and other nutrients are gaining popularity in the ruminant feed industry. The purpose of encapsulation is to provide protection from premature digestion in the rumen, making it possible to increase bioavailability of the core ingredient in the small intestine. Encapsulated products are more effective at delivering a targeted amount of a limiting nutrient than the traditional methods of heat or chemically treating protein, which result in an excess supply of other nutrients. The main limitation of feeding encapsulated products is cost. These products are expensive because of the cost of the film forming/encapsulating materials used. Wheat gluten is an inexpensive alternative and has natural film-forming capabilities. Processing factors that influence the extent of degradation in the rumen and subsequent uptake in the post-ruminal digestive tract have not been fully elucidated. The objective of our research was to identify the initial processing conditions under which wheat gluten will provide sufficient protection from microbial degradation in the rumen. Temperature and pH, in particular, have a large effect on the final properties of the film because of their ability to alter the protein structure of the wheat gluten.
Keywords: Cattlemen& #x27; s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen& #x27; s Day; Beef; Wheat gluten; pH; Rumen microorganisms